CUCA LEGAL PROJECT: MENTAL HEALTH CARE PRACTICES FOR UNIVERSITY STUDENTS - de Muros Xavier, Alessandra (LINKSCIENCEPLACE, 2026)
This article deals with the Cuca Legal Project, developed by the Coordination of Student Assistance and the Field Psychology Department of the Fluminense Federal University (UFF) located in Campos dos Goytacazes. The Project addresses the growing demand for mental health care from the academic community, especially undergraduate students, with complaints about anxiety, depression, and suicide attempts. It proposes to develop a cycle of four semester meetings in order to contribute to the prevention of situations that promote the emotional sickness of university students, the consequent evasion or retention motivated by this issue and to be added to the municipal initiatives of prevention to the suicide.